2021
DOI: 10.1017/s0007114521000192
|View full text |Cite
|
Sign up to set email alerts
|

Profiling inflammatory cytokines following zinc supplementation: a systematic review and meta-analysis of controlled trials

Abstract: Chronic inflammation has been considered as the main cause of chronic diseases. Zn has anti-inflammatory effects by decreasing the expression of inflammatory markers. The present systematic review and meta-analysis study aims to evaluate the impact of Zn supplementation on inflammation. Pubmed (Medline), Scopus, Web of Science, and Embase databases were searched up to December 10th, 2020. Randomized placebo-controlled trials have investigated the effects of Zn supplementation on serum/plasma levels of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Moreover, vitamins D and A, selenium, flavonoids, zinc, and unsaturated fatty acids can alleviate inflammatory response in patients with COVID-19 via inhibiting the activation of nuclear factor kappa-B (NF-κB), hence reducing the production of pro-inflammatory cytokines, such as IL-6 and TNF-α. However, foods with higher glycemic load, carbohydrates, saturated fatty acids, and processed foods are found to disrupt the homeostasis of gut microbiota and are positively related to inflammation conditions in COVID-19 patients ( Faghfouri et al, 2020 , 2021 ; Zabetakis et al, 2020 ). In addition, appropriate intake of specific dietary fiber ( Zhao et al, 2018 ), promote the growth of beneficial bacteria in the intestine, which may reduce the risk of SARS-CoV-2 infection ( Kalantar-Zadeh et al, 2020 ; Merino et al, 2021 ).…”
Section: Preventive Measures For Long-term Gi Injury Induced By Sars-...mentioning
confidence: 99%
“…Moreover, vitamins D and A, selenium, flavonoids, zinc, and unsaturated fatty acids can alleviate inflammatory response in patients with COVID-19 via inhibiting the activation of nuclear factor kappa-B (NF-κB), hence reducing the production of pro-inflammatory cytokines, such as IL-6 and TNF-α. However, foods with higher glycemic load, carbohydrates, saturated fatty acids, and processed foods are found to disrupt the homeostasis of gut microbiota and are positively related to inflammation conditions in COVID-19 patients ( Faghfouri et al, 2020 , 2021 ; Zabetakis et al, 2020 ). In addition, appropriate intake of specific dietary fiber ( Zhao et al, 2018 ), promote the growth of beneficial bacteria in the intestine, which may reduce the risk of SARS-CoV-2 infection ( Kalantar-Zadeh et al, 2020 ; Merino et al, 2021 ).…”
Section: Preventive Measures For Long-term Gi Injury Induced By Sars-...mentioning
confidence: 99%
“…IL-6 and IL-1β are the major pro-inflammatory cytokines that innate immune cells secrete [ 124 ]. A meta-analysis conducted by Faghfouri et al [ 129 ] indicated that zinc supplementation can decrease IL-6 levels, and another former study shows that IL-6 induces low zinc ion availability by modulating MT gene expression [ 130 ].…”
Section: Zinc and Atherogenic Cellsmentioning
confidence: 99%
“…After the TCR trigger, certain zinc transporters, such as ZIP-6 and ZIP-8, are up-regulated and induce a rise in cellular zinc concentration, which is directly involved in T cell activation [ 137 , 138 ]. On the other hand, the cytokine-mediated signaling pathway is regulated by IL-2, and according to Faghfouri et al, zinc can increase IL-2 levels [ 129 ]. IL-2 stimulation can induce T cell proliferation and development through three different signaling pathways: Janus kinase 1/3 (JAK1/3)- signal transducer and activator of transcription 5 (STAT5), ERK1/2, and phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) [ 124 ].…”
Section: Zinc and Atherogenic Cellsmentioning
confidence: 99%
“…Moreover, some of the nutrients including vitamins D and A, zinc, selenium, flavonoids, and unsaturated fatty acids can reverse inflammatory conditions in these patients, especially by affecting nuclear factor kappa-B (NF-κB), which is the main production regulator of pro-inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). However, foods with higher glycemic load, simple carbohydrates, saturated fatty acids, processed foods, and red meats found in Western diets are positively associated with inflammation in COVID-19 (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%